Shari'a Courts in the Ottoman Empire Before the Tanzimat. (November 2019) - Aykan, Yavuz; Ergene, Boğaç
This article describes the history, features and functions of the Islamic law courts in the Ottoman Empire before the Tanzimat era. After briefly surveying of the roots of this institution in pre-Ottoman settings, the article focusses on how Ottoman administrators and juridical experts built on this legacy. Later, the article discusses the modern scholarly literature on the court in a way to reflect on its prevalent tendencies.